2017
DOI: 10.1038/s41598-017-13217-2
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale transport of PM2.5 in the lower troposphere during winter cold surges in China

Abstract: A comprehensive investigation using the air quality network and meteorological data of China in 2015 showed that PM2.5 driven by cold surges from the ground level could travel up to 2000 km from northern to southern China within two days. Air pollution is more severe and prominent during the winter in north China due to seasonal variations in energy usage, trade wind movements, and industrial emissions. In February 2015, two cold surges traveling from north China caused a temporary increase in the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 42 publications
0
34
0
1
Order By: Relevance
“…The local control and prevention of pollution mainly focuses on the relocation of heavily polluted enterprises or on regulating cars. However, PM 2.5 pollution does not only come from local emissions, but is also influenced by meteorological conditions, such as wind direction and speed [10]. Local governments cannot mitigate pollution by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…The local control and prevention of pollution mainly focuses on the relocation of heavily polluted enterprises or on regulating cars. However, PM 2.5 pollution does not only come from local emissions, but is also influenced by meteorological conditions, such as wind direction and speed [10]. Local governments cannot mitigate pollution by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In winter, Korea and China are located on the downwind of winter monsoons. Wang et al [12] reported that Southeast China was affected by long-range transported pollutants from Northern China during the cold surges. A similar behavior was also observed in Korea in winter.…”
Section: Introductionmentioning
confidence: 99%
“…e air pollution is composed of multiple pollutants, which are mainly attributed to power plants, domestic pollutants, industry, and vehicle exhaust [9,[15][16][17]. Meteorological conditions are also important in modulating the distribution of atmospheric pollutants in the BTH [18][19][20][21][22]. Many studies have concluded that high relative humidity is conducive to secondary growth of pollutants, worsening air quality [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to local emissions, the contribution of regional transport mainly depends on wind direction [19]. Taking Beijing as an example, southerly winds are more likely associated with severe air pollution than other wind directions because a portion of the pollutants and warm humid air can be carried from upwind areas to the city [18,20,23,24,[27][28][29][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation